The Trinity among the nations : the doctrine of God in the majority world - Green, Gene L.; Pardue, Stephen T.; Yeo, Khiok-Khng (2015)
Though the global center of Christianity has been shifting south and east over the past few decades, very few theological resources have dealt with the seismic changes afoot. The Majority World Theology series seeks to remedy that lack by gathering well-regarded Christian thinkers from around the world to discuss the significance of Christian teaching in their respective contexts. The Trinity among the Nations focuses on Christian understandings of the character and work of God in various contexts. The contributors highlight global trends in trinitarian theology in relation to historic Christian confessions, especially the Nicene Creed, and draw out the rich implications of the doctrine of God for the church and Christian living today.
Introduction : Trinity 101 : kaleidoscopic views of God in the majority world / K.K. Yeo -- One God in Trinity and Trinity in unity / Gerald Bray -- Beyond "homoiousios" and "homoousios" : exploring North American indigenous concepts of the shalom unity of God / Randy S. Woodley -- The Trinity in Africa : trends and trajectories / Samuel Waje Kunhiyop -- The Trinity as gospel / Antonio González -- Learning to see Jesus with the eyes of the Spirit : the unlikely prophets of God's reign / C. Rosalee Velloso Ewell -- Asian reformulations of the Trinity : an evaluation / Natee Tanchanpongs -- Motherliness of God : a search for maternal aspects in Paul's theology / Atsuhiro Asano -- How to understand a biblical God in Chinese : toward a cross-cultural biblical hermeneutics / Zi Wang.
Includes bibliographical references and indexes.
Master record variable field(s) change: 650
Keywords: God (Christianity); Trinity; Religions; RELIGION -- Christian Theology -- General; Religions; Trinity; Electronic books